The Effectiveness of Lemongrass (Cymbopogon Nardus) Aromatherapy on the Level of Labor Pain in the Active Phase 1 - Andarwulan, Setiana; Waroh, Yuni Khoirul; Hubaedah, Annah (Basic and Applied Nursing Research Journal, 2023)
Background: Labour pain causes hyperventilation, increasing the need for oxygen and blood pressure and reducing intestinal motility and urinary bladder. These conditions will interfere with uterine contractions, which can cause uterine inertia, prolonged labour, inadequate baby oxygenation that results in foetal distress, and maternal and/or foetal death. if labour pain is not treated. Aromatherapy is a therapeutic action that uses essential oils. which is beneficial in improving one's physical and psychological condition to be better. Each essential oil has unique pharmacological effects, such as antibacterial, antiviral, sedative, and stimulates the adrenals. Methods The type of research used in this research is quantitative with a quasi-experimental research design. The research design used was a two-group prepost-test design, a research activity that gave an initial test (pretest) before treatment, after treatment, and then a final test (post-test). The population in this study were all 29 primigravida mothers. The sample was 21 mothers with primigravida. The independent variable in this study was lemongrass aromatherapy, which was measured using standard operating procedures for aromatherapy. The dependent variable in this study was the reduction in pain measured using the NRS scale. The data analysis technique used was univariate data analysis using frequency descriptions and bivariate statistical tests using Wilcoxon signed. Results: The value of p = 0.002 (α < 0.05) was obtained. Therefore, it was concluded that there were differences in pain changes before and after the lemongrass aromatherapy group. Giving lemongrass aromatherapy to pain in the first stage of labour is effective. Conclusion: A woman giving birth during the first active phase needs support to maintain her motivation to birth normally and cope with any discomfort she may experience. Lemongrass aromatherapy, given as a gift, can be used to ease the discomfort of labor, improving both the mother's experience and her ability to trust the process.